Bridging Language Learning and Cognitive Growth: The Power of Situated Learning and Task-Based Language Teaching in Modern Education - Yao, Cheng; Kanjanakate, Supawadee; Jantharajit, Nirat (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2024)
The study explores the effects of a hybrid instructional approach combining Situated Learning (SL) and Task-Based Language Teaching (TBLT) on the executive functions and cognitive abilities of fourth-grade students learning English as a second language (ESL). Method: An experimental design was employed, with students divided into control and experimental groups. The experimental group participated in four weeks of SL and TBLT, while the control group received traditional instruction. Pre-test and post-test measures were taken using the Executive Function Assessment Scale (EFPS) and the Cognitive Abilities Scale (CAS). Results: Although the executive function (M=158.16, t=-14.224, p<0.05) and cognitive ability (M=133.28, t=-11.835, p<0.05) of the students in the control group were improved, the improvement was small. However, the executive function (M=161.88, t=-18.047, p<0.05) and cognitive ability (M=137.04, t=-19.591, p<0.05) of the students in the experimental group were significantly improved. Conclusions: The combination of SL and TBLT significantly enhances both executive functions and cognitive abilities in primary students, indicating the effectiveness of this instructional approach in promoting cognitive development through real-world, task-based activities.